Information Factor in the Dynamics of Contemporary Geopolitical Processes - A. V. Vilovatykh (Сравнительная политика, 2015)
Th e role of information in shaping geopolitical situation needs a greater academic attention, because the infl uence of external actors in favour of theor political preferences forms the vectors of state development. Modern world’s turbulence is based on technologies of managing social reality. It requires a principally new methodology in evaluating and forecasting geopolitical processes. Nowadays it makes sense to speak of information factor of geopolitical dynamics, which shapes a new quality of geopolitical space.